2022
DOI: 10.1038/s41598-022-12898-8
|View full text |Cite
|
Sign up to set email alerts
|

Predictive performance of different NTCP techniques for radiation-induced esophagitis in NSCLC patients receiving proton radiotherapy

Abstract: This study aimed to compare the predictive performance of different modeling methods in developing normal tissue complication probability (NTCP) models for predicting radiation-induced esophagitis (RE) in non–small cell lung cancer (NSCLC) patients receiving proton radiotherapy. The dataset was composed of 328 NSCLC patients receiving passive-scattering proton therapy and 41.6% of the patients experienced ≥ grade 2 RE. Five modeling methods were used to build NTCP models: standard Lyman–Kutcher–Burman (sLKB), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…A recently published study compared the predictive performance of different modeling methods in radiation-induced esophagitis. The researcher reported that the least absolute shrinkage and selection operator (LASSO-MLR) performed best in radiation-induced esophagitis prediction (AUC=0.79) ( 35 ). Furthermore, differentiation between radiation pneumonitis and immune checkpoint inhibitor (ICI)-induced pneumonitis is also very important when radiotherapy is combined with ICI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study compared the predictive performance of different modeling methods in radiation-induced esophagitis. The researcher reported that the least absolute shrinkage and selection operator (LASSO-MLR) performed best in radiation-induced esophagitis prediction (AUC=0.79) ( 35 ). Furthermore, differentiation between radiation pneumonitis and immune checkpoint inhibitor (ICI)-induced pneumonitis is also very important when radiotherapy is combined with ICI treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The far more interesting impact on patient selection is from the uncertainty of the NTCP model itself. While there is no consensus on the optimal NTCP model, we selected the LKB model because it is still the most commonly used NTCP model in radiotherapy, and its non-inferiority to the complex NTCP model has been demonstrated in our previous study (Chen et al 2022). We are planning to investigate the impact of the combined dose and model uncertainty on model-based patient selection in our future study.…”
Section: Discussionmentioning
confidence: 99%
“…The real treatment plan is more complicated than that in the IEC62667 cases. Dose calculation [26], the beam model [27], and different techniques [28] are carefully considered by the clinical team of Shanghai Ruijin Hospital. Figure 13 shows a typical measurement result.…”
Section: End-to-end Test and Third-party Inspectionmentioning
confidence: 99%